2017
DOI: 10.1055/s-0037-1606324
|View full text |Cite
|
Sign up to set email alerts
|

Personal Listening Devices in Australia: Patterns of Use and Levels of Risk

Abstract: Personal listening devices (PLDs) have the potential to increase the risk of noise-induced hearing loss (NIHL) for users. The present study aimed to investigate the nature and extent of the risk posed, by describing the user profile of a PLD population, identifying listening habits of that population, and examining whether PLD risk status is associated with hearing damage. A sample of 4,185 Australian PLD users completed an online survey about listening behaviors and hearing health. Listeners were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Such high music levels are typical when trying to drown out loud background noise [ 163 ]. In ostensibly quieter Australian environments, Gilliver et al [ 168 ] reported that about 10% of PLD users exceeded the NIOSH REL. For Israeli teens, that number was about 25% [ 169 ], while 44% of Canadian teens self-reported loud PLD use [ 81 ].…”
Section: Loud Music and Leisure Noise Is A Common Cause Of Permanent Hearing Loss Tinnitus And Hyperacusismentioning
confidence: 99%
“…Such high music levels are typical when trying to drown out loud background noise [ 163 ]. In ostensibly quieter Australian environments, Gilliver et al [ 168 ] reported that about 10% of PLD users exceeded the NIOSH REL. For Israeli teens, that number was about 25% [ 169 ], while 44% of Canadian teens self-reported loud PLD use [ 81 ].…”
Section: Loud Music and Leisure Noise Is A Common Cause Of Permanent Hearing Loss Tinnitus And Hyperacusismentioning
confidence: 99%
“…PLL was measured by asking to select their typical setting on the volume control from 1 to 15 steps while listening to the provided music, and the volume at the setting was converted to dB according to Min's [24] study. For measuring PLL, many researchers assessed it using a self-reported questionnaire because of difficulties while listening to music with earphones [11,25]. However, the validity of self-reported method for PLL measurements has not yet been established, and is unclear how well they reflect actual PLL [21].…”
Section: Q2mentioning
confidence: 99%
“…Nguyen et al, 2018 [32] Hearing Survey accessible online open to all Australians residents over the age of 15 yrs.…”
Section: Three and Twenty-five Students Participatedmentioning
confidence: 99%